Cajanus cajan – a source of PPARγ activators leading to anti-inflammatory and cytotoxic effects. Issue 9 (6th September 2016) - Schuster, Roswitha; Holzer, Wolfgang; Doerfler, Hannes; Weckwerth, Wolfram; Viernstein, Helmut; Okonogi, Siriporn; Mueller, Monika
Abstract : Cajanus cajan is an important legume crop in the human diet in many parts of the world. Abstract : Cajanus cajan is an important legume crop in the human diet in many parts of the world. Due to its pharmacological properties, C. cajan is, moreover, used in traditional medicine for treating skin diseases, diabetes, inflammatory disorders and various other dysfunctions. In this study, we focused on the role of peroxisome proliferator-activated receptor gamma (PPARγ) as a potential therapeutic target of Cajanus cajan and its main compounds for the treatment of cancer, inflammation and inflammation-related disorders. The anti-inflammatory potential of C. cajan and its bioactive compounds and their cytotoxicity on the human cervical adenocarcinoma cell line HeLa, the human colorectal adenocarcinoma cell line CaCo-2 and the human breast adenocarcinoma cell line MCF-7 were elucidated. C. cajan and its compounds exerted significant anti-inflammatory activity on lipopolysaccharide-stimulated macrophages, showed good cytotoxic effects on the 3 different cancer cell lines and proved PPARγ activity in vitro . The main active compounds were orientin, pinostrobin and vitexin. Cajaninstilbene acid and pinosylvin monomethylether were identified as novel PPARγ activators. Based on these data, C. cajan provides excellent beneficial medicinal attributes and may be used as a potential food or a pharmaceutical supplement.